COMPATIBILITY OF STATE BORDER GUARD AND NATIONAL ARMED FORCES IN THE STATE OF EXCEPTION OR WAR SITUATION - Mikazans, Arvils; Ignatjevs, Olegs (Border Security and Management, 2023)
National armed forces of the Republic of Latvia in the state of exception or war situation. To achieve the aim, following objectives were defined: to state current status of military training in State border guard, to compare State border guard equipment, armament, procedures and training with National armed forces ones, to make proposals for improvement of current compatibility. Following research methods were used: monographic or descriptive method, document analysis, logic- constructive method, analytic method. Within the topic of military compatibility research, the author thoroughly examined State border guard tasks in military sphere, the cooperation between both institutions and the compatibility of State border guard and National armed forces.